Aspect and slope as determinants of vegetation composition and soil properties in coastal forest backdunes of Eastern Cape, South Africa. (13th July 2016) - Ruwanza, Sheunesu; Shackleton, Charlie M.
Abstract: Coastal sand dune ecosystems are subjected to many stress and disturbance factors that are particularly high in the foredunes compared to the backdunes. Although a few studies have been conducted on eastern coastline sand dunes of South Africa, none have examined the relationship between aspect and slope on vegetation composition and soil properties of coastal forest backdunes. Vegetation and soil sampling were conducted in 11 transects, each with four plots measuring 10 × 10 m, located on the seaward and landward sides and on middle and lower slopes of backdunes of Bathurst coastal forest. A total of 39 species were identified, of which 23 were trees and shrubs, thirteen were forbs and three were grasses. The data show that both aspect and slope had limited influence on vegetation community assemblage and soil properties, but had significant effects on individual species distribution. There was a grass‐dominated community on the middle slope and a tree‐ and shrub‐ dominated community on the lower slope. These two plant communities act as the required coastal forest ecosystem engineer driving variability in soil properties between the slopes, the most prominent being high soil nutrients and moisture in the lower slopes compared to the middle slopes.